Relation between changes in weight parameters and height parameters in prepubertal children: daily weight gain and BMIi changes in relation to linear growth during nutritional rehabilitation of underweight children - Soliman, Ashraf T; Itani, Maya; Jour, Celine; Shaat, Mona; Elsiddig, Suhair; Souieky, Fatima; Al-Naimi, Noora; Alsaadi, Reem K; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Early detection of abnormal weight loss or gain in childhood may be important for preventive purposes. Variable growth response to nutrition rehabilitation have been reported in children with failure to thrive (FTT) who do not have any chronic disease or systematic illness due to different clinical and nutritional approach in their management. Aim of the study: To analyze the association of different body mass index (BMI) and BMI- SDS, to linear growth (Ht-SDS) in different BMI categories of prepubertal children. In addition, we studied the effect of weight changes on linear growth in a randomly selected group of prepubertal underweight children who received nutritional rehabilitation (NR) for 9±2 months. Subjects and methods: 102 children, between 1 and 9 years, followed at the General Pediatric Clinic, between January 2017 to December 2017, because of abnormal weight gain (decreased or increased) which was not associated with any acute or chronic illness were included in the study. Anthropometric measurements included weigh, height, Ht-SDS, BMI, and BMI-SDS. Children BMI-SDS were categorized into 4 groups: Group 1: BMI-SDS -1 but 2. We also evaluated the effects of weight changes on linear growth in a randomly selected group of underweight children who received nutritional counselling and oral nutritional supplementation (n = 51) for 9±months. Results: HT-SDS in children of groups 1 and 2 (underweight and at risk of underweight children) was significantly lower than Ht-SDS of groups 3 and 4 (normal and overweight children). Ht-SDS in children of group 4 was significantly higher than the Ht-SDS of children in group 3. A significant linear correlation was found between BMI-SDS and Ht-SDS in these prepubertal children. Discussion: After nutritional rehabilitation for a year, 55% of underweight children increased their BMI-SDS and 43% increased their Ht-SDS. Children who had weight gain >7g/d, over the whole period of follow-up, (n =14) increased their BMI-SDS and Ht-SDS significantly after versus before NR. The BMI-SDS and Ht-SDS did not increase significantly in the group of children who had weight gain